In-plane compressive strength of plywood reinforced with cotton prepreg - Jakimovska popovska, Violeta; Iliev, Borche (Faculty of design and technologies of furniture and interior-Skopje, 2023)
The aim of this research is to study the in-plane compressive strength of eleven-layered beech plywood reinforced with non-wood material in its structure.Plywood reinforcement was made by inserting certain numbers of sheets of pre-impregnated cotton fabric (cotton prepreg). Methyl alcohol-soluble phenol-formaldehyde resin was used for fabric pre-impregnation as well as for veneer bonding. The thickness of the veneers used in the plywood structure was between 1.5 and 1.85 mm. Different models of plywood were made by changing the position of cotton prepreg reinforcements in the plywood structure. One control model of plywood without reinforcement was made. The in-plane compressive strength of plywood models was tested in five directions: parallel to the face grain, perpendicular to the face grain, and at angles of 22.5°, 45°, and 67.5° to the face grain of the plywood panel. The obtained results showed that the application of cotton prepreg in plywood structures has an impact on the values of the in-plane compressive strength of plywood
Keywords: plywood, reinforcement, cotton fabric, prepreg, pre-impregnated, phenol-formaldehyde resin, compressive strength